PERAN GENDER SEBAGAI VARIABEL MODERATOR DALAM HUBUNGAN SELF-CONTROL DAN IMPULSIVE BUYING PADA PENGGUNA SHOPEE PAYLATER - Izzah, Khalid Ahmad; Widyastuti, Liza Yudhita; Putri, Fildzah Radyah (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2026)
This study aims to analyze the relationship between self-control and impulsive purchasing behavior, with gender as a moderating variable. The sample consisted of 200 respondents selected through purposive sampling technique. Data analysis employed Moderation Regression technique using PROCESS Macro. Based on the analysis results, the self-control variable demonstrated a positive and significant influence on impulsive purchasing behavior (? = 2.1253; t = 4.8621; p < 0.001), indicating that the higher the level of self-control, the higher the value of impulsive purchasing behavior. The gender variable also exerted a significant influence (? = 40.7205; t = 3.6577; p < 0.001), suggesting that there are differences in influence based on gender. Furthermore, the interaction between self-control and gender (SC × M) showed a significant influence with a negative coefficient (? = -1.2243; t = -4.9562; p < 0.001). These findings indicate that gender moderates the relationship between self-control and impulsive purchasing behavior, wherein the influence of self-control tends to weaken in certain gender categories. This research provides theoretical contributions to understanding the dynamics of impulsive purchasing behavior and practical implications for marketers in developing more effective strategies based on consumer gender differences.